Pengelolaan Alokasi Dana Desa untuk Pengembangan Pembedayaan Masyarakat di Desa Panggungharjo - Farah Aruni Aqsati (Resolusi: Jurnal Sosial Politik, 2018)
The purpose of this study is to determine the accountability in terms of planning, management, and accountability of village funds in Panggungharjo Village, Sewon District, Bantul Regency. In addition, it is also to find out the development and empowerment of potential communities in Panggungharjo Village. This research is a qualitative descriptive study through methods of data collection, data reduction and data presentation. Village fund planning is carried out together with the APBDes report and submission of the RAPDes from the village to the district. Management is carried out through meetings between the village head, village secretary, financial division, and development division. The accountability of village fund management is submitted with the APBDes report by the Village Head to the District Head. It then is forwarded from the District Head to the Head Regency of Bantul based on the existed regulation. Developing the potency of the community in Panggungharjo Village includes the establishment of activity units such as BUMDes Panggung Lestari, Bapel JSM, SADEPA, Bumi Panggung and Pakarti.